Organizational climate and its impact on university educational quality - Martínez Prats, Germán; Mapén Franco, Fabiola de Jesús; Ortega Ramírez, Marynor Elena (IJERI: International Journal of Educational Research and Innovation, 2021)
The social commitment of higher education institutions to contribute to the development and well-being of societies is fulfilled through the academic profile of its graduates, which implies the implementation of multiple activities inherent to their substantive functions such as teaching and research but also others aimed at evaluation through its indicators. However, it is recognized that there are psychological and sociological factors that affect the behavior of the various university agents with the respective repercussion on educational quality. Therefore, the objective of this research was to evaluate the organizational climate at the Maya School of Agricultural Studies of the Autonomous University of Chiapas in Mexico and its impact on the Institutional Quality Management System. The sample to support the study was 111 educational actors. The research approach was mixed and the validity of the instruments was carried out through the Cronbach’s Alpha Coefficient whose results in the analysis dimensions ranged between 0.898 and 0.95. The results reflected that the factors that affect the organizational climate to a greater extent are: comfort, motivation, identity, communication, structure, decision-making, leadership, reward, innovation and cooperation in conflict resolution. 24% consider that their contribution and performance work is valued by all educational agents, while 48% consider that their managers lack managerial capacities.